Tidal Flood Handling through Community Participation in Drainage Management System (A case study of the first water board in Indonesia) - ratiwi Adi, Henny P; Wahyudi, Slamet Imam (International Journal of Integrated Engineering, 2018)
Floods always occur in some cities located in coastal areas of Indonesia, including in Kemijen area of Semarang city. This study aimed to analyze the technical, institutional and community participation aspects in the management of drainage system and the influence of BPP SIMA (the first water board in Indonesia) in handling of tidal flood. Primary data in this study were obtained through observation and interviews, while secondary data obtained through the study of documents and literature review. Research results showed that technical aspects of drainage management in Kemijen Semarang, still in refinement. Some of the complementary buildings of primary drainage network are still in development. In the institutional aspect, drainage management is still less than optimal because it is handled by department with a number of personnel were very inadequate. Community participation in flood management is still in the form of measures which have not been fully coordinated with the region, such as raising floor of house, access roads and pumping water elevation. BPP SIMA as water board that is responsible for providing information, training and socialization to the community in the management of drainage, is still not optimal in forming a caring community environment.Â